Peningkatan Minat Belajar Keterampilan Bercerita melalui Gambar Seri Digital pada Siswa Sekolah Dasar - Rohmawati Widya Suyanti; Fittri Puji Rahmawati; Widodo Widodo; Theresia Nurani Istiprijanti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to increase interest in learning storytelling skills through digital series pictures in elementary school students. In this study, we will discuss the application of digital serial images to increase interest in learning storytelling skills using digital serial images and the obstacles that arise during application and solutions to overcome them. The methods of data collection in this study were interviews, documentation, and observation. While the data analysis technique is a qualitative descriptive technique of each cycle. The results of this study can be concluded that the interest in learning storytelling skills obtained has increased from cycle I to cycle II by 19%. Thus it can be concluded that through the media of digital series pictures can increase interest in learning storytelling skills in elementary schools. This can be seen from the presentation of interest in telling stories in Indonesian subjects before the action and after the action in each cycle the results achieved have increased Keywords: Digital Series Pictures, Interest in Learning